Jakarta: A Secular City (A Study of Neosecularization of the Middle Class Muslim Community in Metropolitan Jakarta) - Yusuf, Choirul Fuad (Center for Research and Development of Religious Literature and Heritage, 2015)
Originally, this paper is a summative work of the writer’s research conducted in 2013-2014, entitled “Neo-sekularisasi: Studi Sekularisasi pada Komunitas Muslim Kelas Menengah Metropolitan Jakarta” (Neo-secularization: A Study of Secularization at the Middle Class Muslim Community in Metropolitan Jakarta). This study tries to portray of how the role of Islam as a religion has been treated or internalized by its followers, particularly amongst the middle class Muslim in Jakarta as the metropolitan. In other word, the writer wants to explicate of how the middle class Muslim Jakarta internalized and implemented their religious teachings adhered. Using the mixed methodology, the study highlights a numerous conclusions of the findings. First, at the institutional dimension, secularization appeared in the form of religious decline of the religious institution, decline of religious leaders, and religious transformation. Second, at the normative dimension, secularization manifested in the type of desacralisation, disengagement of religion. While at the cognitive dimension, secularization has been being crystallized as religious segmentation and secularism. But, above all, the type, process, and trend of the secularization occurred amongst the middle class of Muslim community is different for the secularization experienced commonly in the West.